Are Economists Rational? On the Rationality of the 'Rational Choice' Paradigm - Johannes Binswanger (Verein für Socialpolitik, 2010)
Today, an overwhelming part of academic analysis is based on the rational choice paradigm. This is true, in particular, for theoretical analyses; but it also holds for empirical analyses as far as they are based on a structural model. It also holds in spite of the existence of the behavioral economics paradigm. In this paper I ask whether the methodological restriction of rational choice is really in the interest of an efficient production of knowledge. Since rational choice is such a universal paradigm in economics, it holds, in fact, a monopoly. This would be desirable if there were a case for a natural monopoly. I argue, however, that this is unlikely to be the case and that more competition between different paradigms would increase the productivity of the economics profession. This increased competition will not simply occur by itself but requires a change in institutions. I discuss several ways, how increased competition between different methodologies could be implemented in practice. I also discuss how the restriction on the rational choice methodology may reflect a form of non-Bayesian judgment of economic researchers themselves.
Keywords: A11; B40; D00; 330; Arbitrariness; Bayesian updating; causality; competition; methodology; parsimony; rational choice